2015
DOI: 10.1016/j.renene.2015.03.083
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the influence of blade helicity on the performance characteristics of vertical axis tidal turbines

Abstract: a b s t r a c tPrevious research has shown that helical vertical axis turbines exhibit lower torque fluctuation levels than straight-bladed turbines; however little is known of the impact of blade helicity on turbine performance characteristics. To investigate these relationships the hydrodynamic characteristics of straight and helical-bladed vertical axis turbines were investigated using Three-Dimensional (3D) Computational Fluid Dynamics (CFD) models using a commercial Unsteady Reynolds Averaged Navier-Stoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 14 publications
1
27
0
4
Order By: Relevance
“…The k-ω SST turbulence model was also used in its fully turbulent formulation as it is commonly used to simulate turbine performance [2,4,[8][9][10][11][12][13][14] due to its ability to model both the boundary layer and the free stream regions. Research has shown that it can accurately predict flow separation and adverse pressure gradients as transport effects are included into the formulation of the eddy-viscosity equations [15,17].…”
Section: Turbulence and Boundary Layer Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The k-ω SST turbulence model was also used in its fully turbulent formulation as it is commonly used to simulate turbine performance [2,4,[8][9][10][11][12][13][14] due to its ability to model both the boundary layer and the free stream regions. Research has shown that it can accurately predict flow separation and adverse pressure gradients as transport effects are included into the formulation of the eddy-viscosity equations [15,17].…”
Section: Turbulence and Boundary Layer Modelingmentioning
confidence: 99%
“…The 3D computational domains were generated to isolate the turbine from any boundary effects; with all boundary conditions outlined in Figure 6 and Table 2, as determined by the systematic domain size independence studies outlined in Section 2.5. Both Turbines A and B were assumed to operate at sufficient depths to ignore free surface effects, allowing the use of symmetry to reduce domain size [2,8,13,14]. Full and half domains were generated, with the half domain split along the horizontal mid plane.…”
Section: Computational Fluid Dynamics (Cfd) Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts illustrate the complexity of the flow around cross-flow water turbines. The computational study of [20] presents the influence of blade helicity on the performance of vertical axis tidal turbines. In particular they study two designs of straight blade turbines differing in the blade-strut connection.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this effect, helical rotor has low power output when compared with a straight bladed Darrieus rotor. However, the helicity of rotor increases the self‐starting characteristics of straight bladed Darrieus rotor …”
Section: Configurations Of Cross‐flow Hydrokinetic Turbinesmentioning
confidence: 99%